Ferroic twin domains in metal halide perovskites. (2019) - Liu, Yongtao; Belianinov, Alex; Collins, Liam; Proksch, Roger; Ievlev, Anton V.; Hu, Bin; Kalinin, Sergei V.; Ovchinnikova, Olga S.
Abstract: An emerging family of materials—metal halide perovskites (MHPs)—have made incredible achievements in optoelectronics in the past decade. Owing to its potential role in optoelectronic properties, the ferroic state of MHPs has been investigated by lots of researchers. Here, we review the literature regarding investigations into possible ferroic behaviors in MHPs. We summarize the recent discoveries of ferroic twin domains in MHPs. We examine the ferroelasticity and the ferroelectricity of these twin domains. Several properties relevant to the twin domains are critically analyzed, including crystallographic structure, mechanical variation, chemical variation, etc. Finally, we discussed the effects of these domains on materials' optoelectronic properties and their potential roles in photovoltaic action.